2007
DOI: 10.1152/ajpheart.01282.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in nitric oxide and mitochondrial oxidative stress with site-dependent differential tissue response during anoxic preconditioning in rat heart

Abstract: J. Dynamic changes in nitric oxide and mitochondrial oxidative stress with site-dependent differential tissue response during anoxic preconditioning in rat heart. Am J Physiol Heart Circ Physiol 293: H1457-H1465, 2007. First published June 1, 2007; doi:10.1152/ajpheart.01282.2006.-In this study, dynamic changes in nitric oxide (NO) and mitochondrial superoxide (O 2 •Ϫ ) were examined during anoxic preconditioning (AP) in rat heart model. AP and anoxia-reoxygenation (A/R) were performed on isolated hearts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…To confirm if the alteration of O 2 - production increase the oxidative damage in ISO-CA, oxidative damage levels of DNA in Con (n = 4) and ISO- CA (n = 4) were measured using single-cell gel electrophoresis assay (comet assay) as previously described [20]. Isolated cerebral artery SMCs (n = 4 in each group) were mixed in 300 μl of low-melting point agarose (1% in PBS).…”
Section: Methodsmentioning
confidence: 99%
“…To confirm if the alteration of O 2 - production increase the oxidative damage in ISO-CA, oxidative damage levels of DNA in Con (n = 4) and ISO- CA (n = 4) were measured using single-cell gel electrophoresis assay (comet assay) as previously described [20]. Isolated cerebral artery SMCs (n = 4 in each group) were mixed in 300 μl of low-melting point agarose (1% in PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Ding et al (18) showed that IH upregulated the baseline level of iNOS mRNA and protein expression, leading to an increase in NO production in the isolated heart. Cuong et al (16) studied changes in NO and mitochondrial superoxide during anoxic preconditioning in isolated hearts and single cardiomyocytes. They concluded that the increase in NO production during reoxygenation in the preconditioned animals was attenuated by the iNOS inhibitor.…”
Section: Values Are Means (Sd) Hematological Variables In Nc Hamstermentioning
confidence: 99%
“…The hypothesis that IH causes oxidative stress stems from observations that ischemia-reperfusion (I/R) or anoxia-reoxygenation injury gave rise to reactive oxygen species (ROS) (3,5,20,32,48,75,99). Applicability of this concept to OSA has been shown in several studies, as exemplified by increased exhaled isoprostanes (9,10), blood reactive oxygen metabolites (18), serum malondialdehyde (MDA) (6,52), neutrophil superoxide production (80), and susceptibility of serum LDL to oxidation (80) in OSA.…”
mentioning
confidence: 99%